Comparative Efficacy Of Pharmacotherapy And Combined Psycho-Pharmacotherapy For Correction Of Psychoemotional, Cognitive And Immunological Disorders In Post-Covid Syndrome Among Young Adults (Texas Journal of Medical Science, 2026)
Post-COVID syndrome (PCS) in young adults is characterized by persistent psychoemotional disturbances, cognitive dysfunction, and immune dysregulation